Gestão integrada e sustentável de resíduos sólidos urbanos para municípios de médio porte - Olivo, Valdir Eduardo (2021)
Municipal solid waste is potentially polluting to the environment if it is not properly managed. Over the years, management and management strategies have been adopted by municipal authorities to control and mitigate the impacts caused to the environment and public health. The objective of this thesis was to present a sustainable municipal solid waste management model, based on consolidated references and experiences that can be applie to medium-sized municipalities in the national territory. The work was divided into four stages, i) presenting the current situation of municipal solid waste management in medium-sized municipalities; ii) guidelines for the integrated management of urban solid waste; iii) benchmarking of integrated solid waste management in medium-sized municipalities and iv) government actions to implement integrated management of solid waste in medium-sized municipalities. The methodology used was through the collection of information in the database for steps i) and iii) and systematic review for steps ii) and iv). Stage i) evaluated the performance of 176 medium-sized municipalities in terms of municipal solid waste management. Stage ii) carried out a systematic review and identified 531 articles that address models of integrated sustainable waste management, after filtering, 51 articles were selected that made up the integrated management guidelines. The results showed the role of each party involved to act in the technical, environmental, financial, institutional, political and cultural aspects of municipal management. Stage iii) presented a benchmarking between 5 mediumsized Brazilian municipalities with excellent performance in 2018. The survey identified through 23 indicators a high engagement of the local government for planning issues and institutional arrangements guaranteed by solid local legislation. Stage iv) presented governmental actions at the local level for small and medium-sized municipalities to achieve sustainability in waste management. At the end, the conditions of applicability of these actions in a medium-sized municipality were evaluated. Chapeco, SC, presented favorable conditions for the implementation of these actions, considering that 52% of the actions are already in operation in the municipality. This thesis presented in chronological order through a solid research in scientific publications and database the structuring of a sustainable management model ideal for medium-sized Brazilian municipalities considering the characteristics of the population dimension and demands of the sector, it is recommended to 176 municipalities able to implement this system apply the fourth stage of this thesis and propose the adequacy measures through the revision of the municipal plans for integrated management of urban solid waste.